Edukasi Gizi Seimbang dan Cara Membaca Label Pangan bagi Masyarakat Di Desa Cibanteng, Kabupaten Bogor - Mauludyani, Anna Vipta Resti; Rahmawati, Laeli; Farhan, Muhammad; Napitupulu, Princilya Anggraeni; Azzahra, Devita Fatimah; Anggini, Awanda Wira; Raditya, Vincentius Yolanda Angger; Tobing, Yolanda Dheva Lumban; Anastasya, Setia; Evafroditus, Yuniarta (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2023)
In Indonesia, the number of people suffering from non-communicable diseases is on the rise. The leading cause is unbalanced nutrition. People must be able to choose healthy meals by reading food labels due to the growing quantity of packaged foods on the market. This Serving Lecturer is designed to teach the public about balanced nutrition and how to read nutritional information on food labels to make healthier food choices. On July 31, 2021, the community in Cibanteng Village, Ciampea District, Bogor Regency, received online balanced nutrition and food labelling education. A pre-test and post-test were used to assess public understanding of food labels. As a result, participants gained a better understanding of the principles of a balanced diet, nutritional values, and healthier choices because of this activity. Participants could also choose healthier goods based on the nutritional value information given on the packaging during the practice session. Balanced nutrition and food label education activities can help people eat healthier foods and stay healthy, active, and productive while avoiding disease.